Non-severe thermal burn injuries induce long-lasting downregulation of gene expression in cortical excitatory neurons and microglia - Ong, Rebecca C. S.; Beros, Jamie L.; Fuller, Kathy; Wood, Fiona M.; Melton, Phillip E.; Rodger, Jennifer; Fear, Mark W.; Barrett, Lucy; Stevenson, Andrew W.; Tang, Alexander D. (Frontiers in Molecular Neuroscience, 2024)
Burn injuries are devastating traumas, often leading to life-long consequences that extend beyond the observable burn scar. In the context of the nervous system, burn injury patients commonly develop chronic neurological disorders and have been suggested to have impaired motor cortex function, but the long-lasting impact on neurons and glia in the brain is unknown. Using a mouse model of nonsevere burn injury, excitatory and inhibitory neurons in the primary motor cortex were labelled with fluorescent proteins using adeno-associated viruses (AAVs). 5 weeks following the burn injury, virus labelled excitatory and inhibitory neurons were isolated using fluorescence-activated cell sorting (FACS). In addition, microglia and astrocytes from the remaining cortical tissue caudal to the motor cortex were immunolabelled and isolated with FACS. Whole transcriptome RNA-sequencing was used to identify any long-lasting changes to gene expression in the different cell types. RNA-seq analysis showed changes to the expression of a small number of genes with known functions in excitatory neurons and microglia, but not in inhibitory neurons or astrocytes. Specifically, genes related to GABA-A receptors in excitatory neurons and several cellular functions in microglia were found to be downregulated in burn injured mice. These findings suggest that non-severe burn injuries lead to long lasting transcriptomic changes in the brain, but only in specific cell types. Our findings provide a broad overview of the long-lasting impact of burn injuries on the central nervous system which may help identify potential therapeutic targets to prevent neurological dysfunction in burn patients.